2019
DOI: 10.1111/1471-0528.15908
|View full text |Cite
|
Sign up to set email alerts
|

Early life famine exposure to the Great Chinese Famine in 1959–1961 and subsequent pregnancy loss: a population‐based study

Abstract: Objective To explore the relation between famine exposure in early life and subsequent pregnancy loss, including stillbirth, and spontaneous abortion in adulthood. Design A population‐based, partly ecological study. Setting and population Individual data of 58 601 females born around the time of the Great Chinese Famine in 1959–1961. Methods Associations between the famine exposure in early life and pregnancy loss (stillbirth and spontaneous abortion) in adulthood were analysed using negative binomial regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Extended drought may also lead to famine, exposure to which is widely recognized as a significant cause of adverse pregnancy outcomes, subsequent chronic diseases later in life, and even intergenerational health impacts. [105][106][107][108][109].…”
Section: Extreme Weather Eventsmentioning
confidence: 99%
“…Extended drought may also lead to famine, exposure to which is widely recognized as a significant cause of adverse pregnancy outcomes, subsequent chronic diseases later in life, and even intergenerational health impacts. [105][106][107][108][109].…”
Section: Extreme Weather Eventsmentioning
confidence: 99%
“…Consistent with previous research on Chinese famine, which lasted for 3 years from 1969 to 1961 with exact start and end time points [14,15]. Participants born before 1942 were categorized as the adult exposed group and served as the reference group for the study.…”
Section: Famine Definitionmentioning
confidence: 98%
“…Hayward et al (14) and Rickard et al (55) find evidence that women born in years with low local crop yields have a reduced reproductive success. Zhang et al (56), using self-reported data, find that women affected by the great Chinese famine in infancy are more likely to report stillbirths, but find no association with spontaneous abortion. Lumey (57) reports no impact on long-term fertility of exposure to the Dutch famine in the Second World War, and Lumey and Stein (58) do not find any significant effect on age at first delivery or proportion of childless women following early-life exposure to the same event.…”
Section: Theoretical Mechanismsmentioning
confidence: 99%